Real‐world short‐term effectiveness of ustekinumab in 305 patients with Crohn's disease: results from the ENEIDA registry. Issue 3 (20th June 2019) - Iborra, M.; Beltrán, B.; Fernández‐Clotet, A.; Gutiérrez, A.; Antolín, B.; Huguet, J.M.; De Francisco, R.; Merino, O.; Carpio, D.; García‐López, S.; Mesonero, F.; Navarro, P.; et al.
Summary: Background: There are limited data of ustekinumab administered according to the doses recommended in the UNITI studies. Aim: To assess the real‐world, short‐term effectiveness of ustekinumab in refractory Crohn's disease (CD) Methods: Multicentre study of CD patients starting ustekinumab after June 2017 at the recommend dose (260, 390 or 520 mg based on weight 6 mg/kg IV week 0 and 90 mg subcutaneously week 8). Values for Harvey‐Bradshaw Index (HBI), C‐reactive protein (CRP) and faecal calprotectin (FC) were recorded at baseline and at weeks 8 and 14. Demographic and clinical data, previous treatments, AEs and hospitalisations were documented. Possible predictors of clinical remission were examined. Results: Three hundred and five patients were analysed (≥2 previous anti‐TNFα therapies 64% and vedolizumab 29%). At baseline, 217 (72%) had an HBI >4 points. Of these, 101 (47%) and 126 (58%) achieved clinical remission at weeks 8 and 14, respectively. FC levels returned to normal (<250 µg/g) in 46% and 54% of the patients at weeks 8 and 14 respectively. CRP returned to normal (<3 mg/L) in the 35% and 41% of the patients at week 8 and 14 respectively. AEs were recorded in 38, and 40 patients were hospitalised. Intolerance to the most recent anti‐TNF agent and fewer previous anti‐TNF agents were associated with clinical remission at week 14. Endoscopic severity was associated with poor response. Conclusion: This is the first study to show the real‐world effectiveness and safety of ustekinumab administered according to the recommended induction regimen in a cohort of highly refractory CD patients.